Analysis of x-ray emission and electron dynamics in a capillary-guided laser wakefield accelerator - J. Ju (2014)
The dynamics of electron acceleration driven by laser wakefield inside a 30.5 mm long dielectric capillary tube is analyzed using radiation emitted in the x-ray range. 3D particle-in-cell simulations, performed with parameters close to the experimental ones, show that in long plasmas, the accelerated electrons catch up and finally overrun the driving laser owing to a higher velocity of the electrons in the plasma. The electrons are then transversely scattered by the laser pulse, and penetrate the capillary wall where they generate bremsstrahlung radiation, modeled using geant4 simulations. The signature of bremsstrahlung radiation is detected using an x-ray camera, together with the betatron radiation emitted during electron acceleration in the plasma bubble. The reflection of betatron radiation from the inner capillary surface also accounts for a fraction of the observed signal on the x-ray camera. The simulation results are in agreement with the experimental ones and provide a detailed description of the electron and radiation properties, useful for the design of laser wakefield accelerators or radiation sources using long plasma media.